How Application Ease The Assessment Process in EFL Classroom - Savitri, Dian; Akmal (Elite : English and Literature Journal, 2023)
The learning process carried out in Indonesia is still dominated by large classes. It contains more than 20 students. This situation sometimes makes it difficult for teachers to conduct assessments because assessing and evaluating each student takes much time. Nowadays, the assessment process is quite diverse; teachers do not only do paper-based tests but can use application assistance. This study aims to see how well the Pintar Apps help teachers conduct student assessments. The method used in this study is qualitative, with instruments in the form of class observations and interviews. The subjects were 15 and 3 English teachers students of SMP Negeri 2 Tayu. The study results revealed that the application helps the student assessment process faster and more accurately. The teacher does not need to check the results of student answers one by one because the system automatically checks them. Pintar Apps as the student assessment application are beneficial for teachers in managing assessment activities in class. Furthermore, Pintar Apps even helps teachers administer the students who have used this application, and there is a list of them for all activities when using this application.